The compleat island traveller a multimedia carousel on Philippine travel. (Department of Tourism fProProjex, 1998)
The CD is a visitor's guide to the Philippines as it tell them where to go, how to go there, what to see, and where to stay, dine and shop. It has over 500 pictures and over 50 video clips.